Developing Noble Morals in Children through Al-Ghazali's Concept of Moral Education - Murdani, Hati; Fauzi, Ahmad (Bestari, 2024)
The cultivation of strong moral principles in youngsters can, indeed, be accomplished through the educational process. The present societal circumstances of adolescents elicit apprehensions, particularly regarding their conduct within social interactions. This essay seeks to analyze Al-Ghazali's notion of moral education in fostering virtuous morals in children. This article, unlike prior study, not only addresses the topic of children's moral education but also outlines the processes for cultivating admirable values in children, the methodologies for imparting moral teachings, and the role of the family environment in this education. This research employs the library study approach, utilizing data analysis techniques that include data gathering, data reduction, data presentation, and conclusion formulation. Al-Ghazali underscored the significance of training and cultivating children's morals through practices and habits aligned with their cognitive development. According to Al-Ghazali's perspectives, the formation of a child's moral character comprises ten steps. The initial method entails explicit instruction utilizing texts from the Quran and hadith that convey the moral principles of the Prophet Muhammad. The second strategy entails indirect means, such narratives that embody moral values or behaviors that incorporate elements of worship. Additionally, Al-Ghazali's framework delineates eleven phases in the development of a child's moral character, emphasizing the importance of fulfilling and adhering to moral commitments.